Participation of androgen and its receptor in sex determination of an amphibian species. - Akira Oike; Maho Kodama; Shigeki Yasumasu; Takashi Yamamoto; Yoriko Nakamura; Etsuro Ito; Masahisa Nakamura (PLoS ONE)
Introduction In the Japanese frog Rana (R.) rugosa the androgen receptor (AR) gene on the W chromosome (W-AR) is barely expressed. Previously we showed that incomplete female-to-male sex-reversal occurred in Z-AR transgenic female frogs. To date, however, there is no report showing that AR with androgens can determine genetically programed male sex fate in any vertebrate species. Here, we examined whether AR together with androgens functions as a sex determinant in an amphibian species. Methods To examine whether complete female-to-male sex-reversal occurs in R. rugosa frogs, we produced AR-transgenic (Tg) and -knockdown (KD) female R. rugosa frogs by the I-SceI meganuclease-mediated gene trap and CRISPR/Cas9 system, respectively. AR-Tg and -KD tadpoles were reared in water containing testosterone (T) at 0 to 7.1 ng/ml. Frozen sections were prepared from the gonads of metamorphosed frogs and immunostained for laminin, Vasa, Pat1a, CYP17 and AR. We also employed PCR analysis to examine Dmrt1, Pat1a and CYP17 expression in the gonads of KD and placebo-KD female frogs. Results Complete female-to-male sex-reversal occurred in the AR-Tg ZW female frogs when a low dosage of T was supplied in the rearing water of tadpoles. However, no sex-reversal was observed in AR-KD ZW female frogs when the gonads were treated with dosages of T high enough to induce complete female-to-male sex-reversal even in wild type frogs. Discussion These results suggest that AR with its androgen ligand functions as a male sex-determinant in the ZW type R. rugosa frogs.